Highly efficient blue all-solution-processed organic light-emitting diodes based on the strategy of constructing a thermally cross-linkable TADF dendrimer. (February 2022) - Sun, Kaiyong; Wu, Jie; Zhu, Lingling; Liu, Hongxiang; Zhou, Yu; Tian, Wenwen; Cai, Zhaosheng; Jiang, Wei; Sun, Yueming
Abstract: Based on the strategy of constructing a new cross-linkable thermally activated delayed fluorescence TADF dendrimer act as the emitter, the blue all-solution-processed organic light-emitting diodes (OLEDs) was developed. Here, two thermally cross-linkable TADF molecules, namely DV-3CzCN and DVCz-3CzCN, are designed and synthesized. Systematic studies demonstrate that the utilization of DVCz-3CzCN can form a stable and uniform thin film by the solution-process, but also effectively suppress the triplet excitons concentration quenching by the intermolecular interaction. Simultaneously, DVCz-3CzCN possesses the sufficient solvent resistance that can afford the subsequently deposition of electron transporting materials by orthogonal solvent. Consequently, the highly efficient blue all-solution-processed device based on DVCz-3CzCN realized a maximum current efficiency (CE), power efficiency (PE) and external quantum efficiency (EQE) of 7.1 cd A −1, 4.5 lm W −1 and 6.8%, respectively, which is eight times higher in device efficiency than corresponding device with the unencapsulated DV-3CzCN. Graphical abstract: Here, a highly efficient blue all-solution-processed OLED was achieved based on the strategy of constructing a thermally cross-linkable TADF dendrimer. Image 1 Highlights: Employing a thermally cross-linkable TADF dendrimer, an efficient blue all-solution-processed OLED was fabricated. DVCz-3CzCN possesses good morphologic stability, sufficient solvent resistance and efficient triplet excitons distribution. The DVCz-3CzCN-based device can afford a high TADF OLED by all solution-process with EQE of 6.8%. The device efficiency of DVCz-3CzCN is eight times higher than the corresponding device with the unencapsulated DV-3CzCN.